2020
DOI: 10.1111/ajag.12851
|View full text |Cite
|
Sign up to set email alerts
|

‘I’d rather die in the middle of a street’: Perceptions and expectations of aged care among Forgotten Australians

Abstract: Objectives: To explore perceptions and expectations regarding aged care among older Forgotten Australians, informing better ways of delivering safe and inclusive care for this group. Methods: In-depth interviews were undertaken with sixteen Forgotten Australians to understand their perspectives, hopes and perceived barriers to receiving appropriate aged care. Qualitative data were analysed using Ritchie and Spencer's framework approach. Results: Participants were highly averse to receiving aged care in residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…1,8 Forgotten Australians are now transitioning to older age and increasingly require some form of aged care support. 10 They are also known to have more rapidly declining physical health, with greater co-morbidity and possibly an increased risk of dementia compared to the general population. 9,11,12 As such, Forgotten Australians reach older age in poorer health and with fewer social supports than the general community.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,8 Forgotten Australians are now transitioning to older age and increasingly require some form of aged care support. 10 They are also known to have more rapidly declining physical health, with greater co-morbidity and possibly an increased risk of dementia compared to the general population. 9,11,12 As such, Forgotten Australians reach older age in poorer health and with fewer social supports than the general community.…”
Section: Introductionmentioning
confidence: 99%
“…Our research has demonstrated a range of concerns about accessing aged care services among Forgotten Australians, including a profound aversion to being 're-institutionalised' in residential aged care and reliving childhood trauma. 10 Specific vulnerabilities from childhood experiences may be re-triggered by a lack of control over institutional practices including group activities, prescribed meals and mealtimes, medications, and closed windows and doors. 1,5,10,13 While participants reported a preference for ageing in place, they noted that home care still introduces a power imbalance requiring levels of trust difficult to generate for trauma survivors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations